Portrait of Jacques-Louis David - Jérôme-Martin Langlois (Wikimedia Commons, 1824)
Notice iconographique issue de Wikimedia Commons. Titre: Portrait of Jacques-Louis David.
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons